A comparison of concurrent cisplatin versus cetuximab with radiotherapy in locally-advanced head and neck cancer: A bi-institutional analysis - Stokes, William A. (Rep Pract Oncol Radiother, 2017)
AIM: To present our experience comparing cisplatin- and cetuximab-based radiotherapy for locally-advanced head and neck squamous cell carcinoma. BACKGROUND: The comparative effectiveness of cisplatin-based chemoradiotherapy (CRT) versus cetuximab-based bioradiotherapy (BRT) for locally-advanced head and neck squamous cell carcinoma (LAHNSCC) continues to be explored. MATERIALS AND METHODS: Outcomes of LAHNSCC patients treated with CRT (125) or BRT (34) at two institutions were compared retrospectively, with attention to overall survival (OS), cancer-specific survival (CSS), locoregional control (LRC), and distant control (DC). Univariate analysis (UVA) using Cox regression was performed to explore the association of intervention with survival and disease control, and multivariate (MVA) Cox regression was then performed to assess the association of intervention with survival. RESULTS: There were significant baseline differences between the CRT and BRT groups with respect to age, race, performance status, N-classification, tobacco history, and human papillomavirus status. UVA demonstrated inferiority of BRT versus CRT with respect to both OS (hazard ratio [HR] 2.19, 95% confidence interval [95%CI] 1.03–4.63, p = 0.04) and CSS (HR 3.33, 95%CI 1.42–7.78, p < 0.01), but non-significantly different outcomes in LRC (HR 0.99, 95%CI 0.37–2.61, p = 0.98) and DC (HR 2.01, 95%CI 0.78–5.37, p = 0.14). On MVA, there was no significant OS difference between interventions (HR 1.19, 95%CI 0.42–3.35, p = 0.74); there were too few events for the other outcomes to draw meaningful conclusions with MVA. CONCLUSIONS: In our retrospective analysis, patients undergoing CRT experienced improved OS and CSS over those receiving BRT; however, disease control did not significantly differ. These findings may inform management of LAHNSCC patients.